Implementation of the problem based learning (PBL) model using ICT-assisted reading text media to increase reading interest in class ii students of SDN 3 gunungsari - Hendarsih, Heni; Nurhidayah, Nunung (Sekolah Pascasarjana UPI, 2023)
The aim of this research is to determine the level of reading interest of class II students after implementing learning using the Problem Based Learning model in Indonesian language subjects at SDN 3 Gunungsari. The background of this research is based on the low reading interest of class II students in Indonesian language subjects with capital letters. In reality, at school, it is still difficult for students to be invited to read, let alone understand the content of the reading. The method that the author uses in this research is the Classroom Action Research (PTK) method. The results of the research can be seen from the level of students' interest in reading through the Problem Based Learning learning model which has increased further. This can be seen through the learning practices that have been carried out. In cycle I, the results of the learning test using the Problem Based Learning model obtained the highest result of 100 and the lowest result of 60 with an average of 84. There were 3 students with scores below the KKM, there were 3 students who managed to get the standard KKM score, then the students who 5 people managed to get a score above the KKM. Meanwhile, in cycle II, the results of student knowledge in learning using PBL were with the highest score of 100 and the lowest score of 60 with an average of 92.7%, thus experiencing an increase of 23.6%. Even though there was 1 student who still got a score below the KKM. There were 8 students who got a score of 100, 2 students who got a score of 80, 1 student who got a score of 60